Market Orientation and Organizational Performance: Is Innovation a Missing Link? - HAN, Jin K. (Institutional Knowledge at Singapore Management University, 1998)
In recent years, a market-oriented corporate culture increasingly has been considered a key element of superior corporate performance. Although organizational innovativeness is believed to be a potential mediator of this market orientation-corporate performance relationship, much of the evidence to date remains anecdotal or speculative. In this context, the authors present a systematic framework to test the postulated "market orientation-innovation-performance" chain. To this end, the direct causality assumption of market orientation on organizational performance is examined with Narver and Slater's (1990) market orientation framework. Moreover, the authors take a componentwise approach and examine how the three core components of market orientation (customer orientation, competitor orientation, and interfunctional coordination) affect the two core components of organizational innovativeness (technical versus administrative) en route to affecting corporate performance. Using banking industry data, the authors empirically test and substantiate innovation's mediating role in the market orientation-corporate performance relationship.